Expert System for Diagnosing Cocoa Diseases Using the Dempster Shafer Method - Annafi Franz; Nurlaila Nurlaila; Putri Yus Andayani (Politeknik Pertanian Negeri Samarinda, 2020)
Indonesia occupies the third position of the largest cocoa producing country in the world, but the challenge faced is that the disease that attacks the cocoa plant causes only 60% of the cocoa production is export-worthy. The Dempster Shafer method can be used to diagnose types of diseases in cocoa plants. The system can be used by cocoa farmers in Indonesia to minimize the attack of cocoa plant diseases, so that yields can be abundant. This research was conducted at P4S Karya insani, Linking. As a research location for 6 months, from September 2018 to March 2019, it includes taking data, analysis, develop the applications, implementation, and testing. Expert system diagnosis of cocoa plant diseases using the dempster shafer method makes it easy for users to know the symptoms and diseases of the cocoa plant so that it can be used in diagnosing cocoa plant diseases.